Pancreatico-gastric fistula arising from IPMN associated with ductal adenocarcinoma of the pancreas: a case report and a literature review - AbuDalu, M.; Munz, Y.; Ohana, G. (Frontiers in Surgery, 2023)
Introduction Intraductal papillary mucinous neoplasm (IPMN) is a distinct entity characterized by papillary proliferations of mucin-producing epithelial cells with excessive mucus production exhibiting various degrees of dysplasia, with cystic dilatation of the main pancreatic duct (MD-IPMN) and/or side branch (SB-IPMN). We report a case of an IPMN that has penetrated the stomach and has differentiated into an adenocarcinoma. Case presentation A 69-year-old female, suffering from chronic pancreatitis of unknown aetiology, visited our outpatient clinic with complaints of sudden loss of weight, diarrhoea, and abdominal pain. She underwent several examinations to evaluate the reasons for her sudden onset of symptoms. A gastroscopy showed an ulcerated lesion covered with mucus. CT and MRCP revealed that the main pancreatic duct (MPD) was dilated to 1.3 cm with a fistula formation between the MPD and the stomach. After a multidisciplinary discussion regarding this case, a total pancreatectomy was proposed. An en bloc total pancreatectomy with gastric wedge resection including the fistula together with splenectomy were carried out. A roux en Y choledochojejunostomy and gastrojejunostomy were performed. Histology results revealed the association of IPMN with invasive carcinoma. Discussion During the last three decades, an increasing number of reports on IPMN of the pancreas have been published. Apparently, fistula formation between IPMN and adjacent organs is possible. Given the CT and endoscopic ultrasonography findings, it appears that in our case a main-duct IPMN formed a pancreatico-gastric fistula. We believe that the adherence of invasive cancer cells contributed to the fistula formation between the pancreas and the stomach. Conclusion This case report provides evidence regarding the possibility of IPMN to become complicated with pancreatico-gastric fistula. Thus, we believe that surgical resection should be considered in the case of MD-IPMN because of their high propensity for malignant transformation.